Idiom Musikal Minangkabau dalam Komposisi Karawitan, Sebuah Analisis Konteks Adaptasi Musikal - Erizon Koto (Gondang: Jurnal Seni dan Budaya, 2017)
The study aims at understanding and analyzing (a) understanding of the terminology of the composition and method of cultivation so that the terms of composition and arrangement can be understood contextually, (b) the mustering of Minangkabau musical idioms developed using Western elements and instruments to become a work of music; (c) Adapting Minangkabau karawitan to Western music concepts in a musical work in Karawitan ISI Padangpanjang. This research is field work, field includes observation, interview, and recording. Work in the laboratory includes processing, selecting, and filtering field data. The method used is qualitative method verivikatif begins with data collection both field, interview, and library then looking for theoretical approach to analyze the data that have been obtained. The results of the analysis show (a) The existence of inappropriate perception of the term compositional terms to be confused with the term arrangement. Cultivation works tend to be done collectively, not purely from the creativity of the owner of the work, but the work of the music on behalf of a person alone. (b) There is the use of Western musical elements and instruments in musical works in the form of harmonious harmonies, homophonic textures and polyphony and the use of flute instruments, alto saxophone, tenor saxophone, trumpet, trombone, tuba, guitar, bass guitar, keyboard and drum set. (c) Minangkabau Karawitan adapts to Western music in an academic context, in ISI Padangpanjang on musical forms.